2020
DOI: 10.1136/rmdopen-2020-001201
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal perforations in patients with rheumatoid arthritis treated with biological disease-modifying antirheumatic drugs in Sweden: a nationwide cohort study

Abstract: ObjectivesTo compare incidence rates of gastrointestinal (GI) perforations between patients with RA and the general population, and between patients treated with tumour necrosis factor inhibitors (TNFi) and non-TNFi biologics.MethodsIn this nationwide cohort study, a total of 63 532 patients with RA, with 26 050 biological treatment episodes (TNFi, rituximab, abatacept or tocilizumab) and 76 304 general population controls, were followed between 2009 and 2017 until the first outcome event. The main outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
(68 reference statements)
1
8
0
2
Order By: Relevance
“…119 120 Overall incidence rates for lower GI perforations (LIP) under TCZ treatment were markedly increased compared with csDMARDs, TNF-inhibitors, RTX 121 or the general population. 122 Two of the included studies were further adjusted for concomitant treatment with GC and NSAIDs 120 121 and two for history of diverticulitis. 120 123 Diverticulitis itself was more often associated with perforation in TCZ exposed patients than in patients treated with other agents.…”
Section: Resultsmentioning
confidence: 99%
“…119 120 Overall incidence rates for lower GI perforations (LIP) under TCZ treatment were markedly increased compared with csDMARDs, TNF-inhibitors, RTX 121 or the general population. 122 Two of the included studies were further adjusted for concomitant treatment with GC and NSAIDs 120 121 and two for history of diverticulitis. 120 123 Diverticulitis itself was more often associated with perforation in TCZ exposed patients than in patients treated with other agents.…”
Section: Resultsmentioning
confidence: 99%
“…Die intestinale Obstruktion ist eher eine Komplikation bei der onkologischen Therapie. Gastrointestinale Infektionen oder Perforationen unter Rituximab wurden bei rheumatologischen Erkrankungen insbesondere in der Kombination mit Steroiden gesehen [40,41]. Zudem kann es durch einen prolongierten Immunglobulin-Mangel zu persistierenden GI-Infektionen, z.…”
Section: Rituximabunclassified
“…Tocilizumab ist ein humanisierter monoklonaler Antikörper gegen den Interleukin-6-Rezeptor zur Behandlung der RA, der systemischen juvenilen idiopathischen Arthritis und der Riesenzellarteriitis. Neben Bauchschmerzen und gastritischen Beschwerden kommt es unter Tocilizumab bei der Behandlung einer RA signifikant häufiger zu einer Perforation im Kolon als unter anti-TNFalpha-Therapie [41,42]. Risikofaktoren hierfür sind höheres Alter (HR 1,16 pro 5 Jahre; 95 % CI 1,10-1,22), Divertikulitis/andere GI-Erkrankungen (HR 3,25; 95 % CI 1,62-6,50) und begleitende Steroid-Einnahme > 7,5 mg/d (HR 2,29; 95 % CI 1,39-3,78) [42].…”
Section: Tocilizumabunclassified
“…Rheumatoid arthritis (RA) is considered a risk factor for GIP because of RA medications, including non-steroidal antiinflammatory drugs (NSAIDs), steroids, and disease-modifying antirheumatic drugs (DMARDs) (4)(5)(6). The inflammation or other processes in RA may be also a risk factor for GIP (4,7). Many studies have reported the comparison of the risk of GIP using medications, including biologic agents, DMARDs, steroids, and NSAIDs (4,5,7).…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is considered a risk factor for GIP because of RA medications, including non-steroidal anti-inflammatory drugs (NSAIDs), steroids, and disease-modifying antirheumatic drugs (DMARDs) ( 4 6 ). The inflammation or other processes in RA may be also a risk factor for GIP ( 4 , 7 ).…”
Section: Introductionmentioning
confidence: 99%